The Definition of Private adn Public Space in Implementation of Qanun Jinayah in Aceh - Faradilla Fadlia; Ismar Ramadani (ADDIN, 2019)
This paper will discuss how the Qanun Jinayah differentiate the concept of private and public space in the implementation of sharia in Aceh. This paper will particularly discuss how private and public space being defined in the Qanun and how broad the scope of this Qanun is. This paper finds that there is no private space in Qanun Jinayah. There are only two conditions that listed in Qanun Jinayah, first, when at the work place, second evidence by the family card. A person who committed to criminal Act (Jarimah) in private and public space, he or she will be punished by Qanun Jinayah. Because of that Government in this case Wilyatul Hisbah and investigator has right to enter a person’s private space if that person is suspected to Jarimah crime. This paper sees that the authority has changed to violate the human right.